6x-2y=6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 6x from both sides of the equation.

-2y=6-6x

Divide each term by -2 and simplify.

Divide each term in -2y=6-6x by -2.

-2y-2=6-2+-6x-2

Cancel the common factor of -2.

Cancel the common factor.

-2y-2=6-2+-6x-2

Divide y by 1.

y=6-2+-6x-2

y=6-2+-6x-2

Simplify 6-2+-6x-2.

Simplify each term.

Divide 6 by -2.

y=-3+-6x-2

Cancel the common factor of -6 and -2.

Factor -2 out of -6x.

y=-3+-2(3x)-2

Cancel the common factors.

Factor -2 out of -2.

y=-3+-2(3x)-2(1)

Cancel the common factor.

y=-3+-2(3x)-2⋅1

Rewrite the expression.

y=-3+3×1

Divide 3x by 1.

y=-3+3x

y=-3+3x

y=-3+3x

y=-3+3x

Reorder -3 and 3x.

y=3x-3

y=3x-3

y=3x-3

y=3x-3

Using the slope-intercept form, the y-intercept is -3.

b=-3

Find the Y-Intercept 6x-2y=6